2014
DOI: 10.1126/science.1251817
|View full text |Cite
|
Sign up to set email alerts
|

Defaunation in the Anthropocene

Abstract: onto ecosystem functioning and human well-being. Much remains unknown about 28 this "Anthropocene defaunation"; these knowledge gaps hinder our capacity to 29 predict and limit defaunation impacts. Clearly, however, defaunation is both a 30 pervasive component of the planet's sixth mass extinction, and also a major driver of 31 global ecological change. 32 33In the past 500 years, humans have triggered a wave of extinction, threat, and local 34 population declines that may be comparable in both rate and magnit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

31
2,455
3
111

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 3,159 publications
(2,746 citation statements)
references
References 152 publications
31
2,455
3
111
Order By: Relevance
“…Pollen grains were counted under 400 × and 1,000 × magnification using Nikon LABOPHOT (Bolivian traps, by WDG) and Nikon Eclipse 50i (Ghanaian traps, by ACMJ) microscopes. Pollen identifications were based on pollen reference collections (University of Leicester, The Open University, University of Amsterdam), pollen atlases and online resources (Bonnefille 1971;Bonefille and Rioellet 1980;Moore et al 1991;Roubik and Moreno 1991;Colinvaux et al 1999;Bush and Weng 2007;Vincens et al 2007;Gosling et al 2013). Target pollen sums (total number of pollen grains counted) for the Bolivian plots were > 100 grains per trap, which resulted in > 2,500 grains per vegetation study plot (Table 1; Fig.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pollen grains were counted under 400 × and 1,000 × magnification using Nikon LABOPHOT (Bolivian traps, by WDG) and Nikon Eclipse 50i (Ghanaian traps, by ACMJ) microscopes. Pollen identifications were based on pollen reference collections (University of Leicester, The Open University, University of Amsterdam), pollen atlases and online resources (Bonnefille 1971;Bonefille and Rioellet 1980;Moore et al 1991;Roubik and Moreno 1991;Colinvaux et al 1999;Bush and Weng 2007;Vincens et al 2007;Gosling et al 2013). Target pollen sums (total number of pollen grains counted) for the Bolivian plots were > 100 grains per trap, which resulted in > 2,500 grains per vegetation study plot (Table 1; Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Biodiversity is widely regarded as important for ecosystem function and services (Hooper et al 2005;Cardinale et al 2012), and consequently the observed loss of biodiversity over recent decades (Benitez-Malvido and Martinez-Ramos 2003;Stuart et al 2004;Dirzo et al 2014) has resulted in many efforts being made to preserve biodiversity. For example, actions have targeted the preservation of individual species (Teich et al 2005), the establishment of areas of conservation priority (Myers et al 2000) and the promotion of re-wilding at a continental scale (Navarro and Pereira 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Direct drivers of change include land‐use change, climate change, invasive alien species, overexploitation, and pollution (Pereira, Navarro, & Martins, 2012; Vitousek, Mooney, Lubchenco, & Melillo, 1997). The loss of biodiversity may alter ecosystem functioning and the delivery of ecosystem services, with major repercussions on human well‐being (Balvanera et al., 2006; Dirzo et al., 2014; Hanski et al., 2012; Mace, Norris, & Fitter, 2012). Although biodiversity is assumed to be critical for providing ecosystem services (Cardinale et al., 2012; De Bello et al., 2010; Harrison et al., 2014), our understanding about the links between biodiversity and individual ecosystem services remains incomplete (Balvanera et al., 2014; Bennett et al., 2015; Isbell et al., 2011; Suding et al., 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The persistence of several species worldwide has been threatened by current levels of anthropogenic disturbances in natural environment to the point that the rate of species extinction is already comparable to mass extinction events of the geological past (Dirzo et al 2014). Among mammals, one in each four species is already threatened, mainly due to habitat loss and degradation.…”
Section: Introductionmentioning
confidence: 99%